Comprehensive analysis of SWEET family genes in Eucalyptus (Eucalyptus grandis). Issue 1 (1st January 2020) - Yin, Qi; Zhu, Li; Du, Pingzhou; Fan, Chunjie; Wang, Jinyan; Zhang, Baolong; Li, Huiling
Abstract: SWEET family genes play an important role in different physiological processes, including sugar transport and adjustments, plant development and environmental adaptability. BLAST tools and Hidden Markov Model-directed sequence alignments in Eucalyptus grandis genome identified 52 Eucalyptus SWEET genes containing MtN3/saliva domain. Out of these, 40 genes encode predicted proteins that have 6 or more transmembrane regions with two MtN3/saliva domains. Six predicted proteins contained only one MtN3/saliva domain, similar to the structure of microbial SemiSWEETs. Of the 52 SWEET candidates, only 45 SWEET family genes were mapped on 8 chromosomes, and most of them showed clustered distribution. The expression profiles revealed that the SWEET genes have different expression in different tissues, showing that they might play different functions in Eucalyptus . Our results explored the evolutionary aspects, provided a systematic description of Eucalyptus SWEET genes and can help researchers to understand the functions of the SWEET family genes in Eucalyptus .